Association of cough with asthma in chronic rhinosinusitis patients - Marino, Michael J. (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVE: To determine whether the complaint of cough in chronic rhinosinusitis (CRS) patients is associated with asthma and if there is a potential predictive value for asthma diagnosis. METHOD: Consecutive patients presenting for initial evaluation at a tertiary rhinology clinic who were diagnosed with CRS were considered for inclusion in a cross‐sectional study. The presence and severity of cough was determined using the 22‐item Sinonasal Outcome Test (SNOT‐22). Subgroup analysis included asthma diagnosis confirmed by pulmonary function testing (PFT) in our institution, and for chronic rhinosinusitis patients with (CRSwNP) and without nasal polyps (CRSsNP). RESULTS: The total study population included 297 patients with a diagnosis of CRS, with 63.9% of patients reporting cough. Physician‐confirmed diagnosis of asthma was made in 38.7% of patients, and confirmed in 69.6% by PFT. Cough was more frequently reported by CRS patients diagnosed with asthma (relative risk [RR] = 1.60, 95% confidence interval [CI], 1.13‐2.25), with sensitivity of 73.9% (95% CI, 65.0%‐81.1%). This remained significant in the CRSsNP subgroup (RR = 2.65, 95% CI, 1.32‐5.30), with sensitivity of 83.3% (95% CI, 70.4%‐91.3%) and specificity of 41.2% (95% CI, 33.2%‐49.8%). Cough was not associated with asthma in CRSwNP patients (RR = 1.26, 95% CI, 0.89‐1.79). Cough severity had poor predication for asthma diagnosis (AUC = 0.60, 95% CI, 0.54‐0.65). CONCLUSIONS: Complaint of cough is associated with diagnosis of asthma in CRS patients. In CRSsNP, complaint of cough was sensitive for asthma diagnosis, although specificity was low. Cough in CRS patients can be multifactorial and asthma may be an important diagnostic consideration. LEVEL OF EVIDENCE: 4.